Wartime culture in Guilin, 1938-1944 : a city at war - Zhu, Pingchao (Lexington Books, 2015)
This book examines the development of wartime culture in the Chinese city of Guilin during the Japanese invasion between 1938 and 1944. Controlled and protected by a nationally powerful Guangxi warlord group, Guilin's liberal atmosphere attracted intellectuals of different social and political backgrounds who engaged in various forms of literary production, making the city a new wartime cultural center.